PEMANFAATAN LUMPUR SPRAY POND INDUSTRI GULA UNTUK NUTRISI PERTUMBUHAN BAKTERI HALOFILIK (The Using of Spray Pond Mud from Sugar Industry for Halophilic Bacteria Growing Nutrient) - Nilawati, Nilawati (Baristand Industri Banda Aceh, 2013)
Mud spray pond is a collection of falling water condenser at processingsugar that forms sludge are accommodated in the spray-pond tub. Mud is still containvapor juice which there are organic materials. Mud is in the sugar mills often called Lemi.Outside the sugarcane milling season, Lemi used as a source of fish and snails feed. Lemicontent protein 1.43%, carbohydrate 0.30%, water 14.14%, ash 69.45% and C organic9,54%. Because it still contains organic material that can be used as nutrients halofilik. Sotherefore it can be used Lemi to reduce Luria Berthani media use in the growing of starterhalofilic. There are 6 kinds of formulations used was 0 ml starter; 100 ml Lemi and 400 mlsalt water (L1), 50 ml starter; 100 ml Lemi and 350 ml salt water (L2), 100 ml starter;100 ml Lemi and 300 ml salt water (L3), 200 ml starter; 100 ml Lemi and 200 ml saltwater (L4), 300 ml starter; 100 ml Lemi and 100 ml salt water (L5) and 400 ml starter;100 ml Lemi and 0 ml salt water (L6). The results of the research that has been done thenthe best formulations for bacterial nutrients haofilik using Lemi was L3 formula that wasmixtured of salt starter with brine 200 Be as much as 300 ml, Lemi 100 ml, 100 ml LBstarter, 1 gram sugar and urea 1 gram. With the N content of 0.10% and 1.261% C, andthe amount of bacteria that grew in the starter halofilik as much as 6.60 x 106 colonies permilliliter